How can policy makers foster innovation? Observations from an analysis of OECD countries. - Kirikkaleli, Dervis; Ozun, Alper; Sari, Arif (Innovation: The European Journal of Social Sciences, 2022)
In this paper, we discuss the main determinants of innovation in OECD countries using annual data covering the period 2006–2015. Panel techniques, including Kao co-integration, fully modified ordinary least squares (FMOLS) and panel Granger causality tests, are implemented to investigate the causal and long-term linkages. Our empirical findings reveal that the macroeconomic environment, business sophistication, quality of the education system, technological readiness and infrastructure have significant and positive impacts on innovation in the long term.